Rapid, targeted and culture-free viral infectivity assay in drop-based microfluidics1. Issue 19 (7th October 2015) - Tao, Ye; Rotem, Assaf; Zhang, Huidan; Chang, Connie B.; Basu, Anindita; Kolawole, Abimbola O.; Koehler, Stephan A.; Ren, Yukun; Lin, Jeffrey S.; Pipas, James M.; Feldman, Andrew B.; Wobus, Christiane E.; et al.
<x xml:space="preserve">Abstract</x> We developed a rapid, targeted and culture-free infectivity assay using high-throughput drop-based microfluidics. The high sensitivity and large dynamic range of our cost effective assay alleviates the need for serial dilution experiments.